TICS aplicadas al turismo: propuesta para el diseño de una página web para la promoción turística de la parroquia Santa Lucía de Las Peñas, cantón Eloy Alfaro, provincia de Esmeraldas - Bonilla Mantilla, Cristina Marcela (2017)
The following research is focused in designing a web page as a tool to promote tourism in the town of Santa Lucía de Las Peñas, located in Eloy Alfaro, province of Esmeraldas. Relevant information justifying the creation of the web page is presented as an introduction. Then the research is presented sequentially differentiating four chapters, the first one is the presentation of important sources needed as the theoretical framework of the investigation; in the second chapter there are surveys which were needed to analyzed and establish the visitor profile in Las Peñas; the next chapter is focused on observation and analysis of interviews made to different representatives of local institutions and organisms, with this information started setting up the creative side and content of the web page; finally the fourth chapter is focused in presenting the design and structure of the final web page with strategies to evaluate it for it is future. Finally there are conclusions and recommendations presented for optimum performance of the web page as a tool to promote tourism in Santa Lucía de Las Peñas.